Multiple sclerosis iPS-derived oligodendroglia conserve their properties to functionally interact with axons and glia in vivo - Mozafari, Sabah; Starost, Laura; Manot Saillet, Blandine; Garcia Diaz, Beatriz; Xu, Yu Kang T; Roussel, Delphine; Levy, Marion J F; Ottoboni, Linda; Kim, Kee Pyo; Scholer, Hans R; Kennedy, Timothy E; Antel, Jack P; et al. (American Association for the Advancement of Science, 2020)
Remyelination failure in multiple sclerosis (MS) is associated with a migration/differentiation block of oligodendroglia. The reason for this block is highly debated. It could result from disease-related extrinsic or intrinsic regulators in oligodendroglial biology. To avoid confounding immune-mediated extrinsic effect, we used an immune-deficient mouse model to compare induced pluripotent stem cell–derived oligodendroglia from MS and healthy donors following engraftment in the developing CNS. We show that the MS-progeny behaves and differentiates into oligodendrocytes to the same extent as controls. They generate equal amounts of myelin, with bona fide nodes of Ranvier, and promote equal restoration of their host slow conduction. MS-progeny expressed oligodendrocyte- and astrocyte-specific connexins and established functional connections with donor and host glia. Thus, MS oligodendroglia, regardless of major immune manipulators, are intrinsically capable of myelination and making functional axo-glia/glia-glia connections, reinforcing the view that the MS oligodendrocyte differentiation block is not from major intrinsic oligodendroglial deficits.
Keywords: Esclerosis múltiple; Multiple sclerosis; Oligodendrocyte differentiation; Remyelination; Axo-glia connection; Glia-glia connection